KINERJA PEGAWAI PADA KANTOR BIRO ADMINISTRASI AKADEMIK KEMAHASISWAAAN (BAAK) UNIVERSITAS NEGERI PADANG - Eka Purnama Sari (Jurnal Bahana Manajemen Pendidikan, 2014)
The goal of this research are to see information aboutthe employee perfomance. The population is 29employeeand the sample is 29 people that taken by population research. The instrument of this research is question with Likert scale modelsthat had tested for validity and reliability. Data analyzed using mean score and performance level. The result of this research are the employee performance in Biro Administrasi Akademik Kemahasiswaan stay in high enough category. Key word : Employee Performance